2011
DOI: 10.1007/s11605-011-1498-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Risk Factors for Delayed Gastric Emptying (DGE) after 387 Pancreaticoduodenectomies with Usage of 70 Stapled Reconstructions

Abstract: The method of alimentary reconstruction affected the occurrence of DGE. The incidence of DGE was less in stapled reconstruction than in hand-sewn reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 40 publications
8
56
3
1
Order By: Relevance
“…However, in our previous study, we already had good reason to consider that stapled reconstruction was easier, more comfortable, and more stable than HS anastomosis on the basis of experience of performing 70 anastomoses using staplers. 10 In conclusion, the results of this RCT showed that use of a CS for duodenojejunostomy in PpPD is an acceptable option that did not increase the risk of DGE.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…However, in our previous study, we already had good reason to consider that stapled reconstruction was easier, more comfortable, and more stable than HS anastomosis on the basis of experience of performing 70 anastomoses using staplers. 10 In conclusion, the results of this RCT showed that use of a CS for duodenojejunostomy in PpPD is an acceptable option that did not increase the risk of DGE.…”
Section: Discussionmentioning
confidence: 60%
“…We hypothesized that the diversity of hand-sewn (HS) anastomosis may be associated with increased risk of DGE and previously conducted a retrospective study to compare the incidence of DGE after stapled duodenojejunostomy and gastrojejunostomy with those after HS reconstruction for pylorus-preserving PD (PpPD) or classic PD in 387 patients undergoing PD. 10 This study showed that the incidence of DGE was lower after stapled reconstruction (n=70) than that after HS reconstruction (n=317) (7.2 vs. 21 %, P<0.001) and with single-layer anastomosis than with double-layer anastomosis (12 vs. 24 %, P= 0.02). However, these results may have been biased because of the retrospective single institution nature of the study that included a variety of surgical procedures and historical changes.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…The potential causes of DGE are decreased plasma motilin concentrations induced by the duodenal resection, pylorospasm after vagotomy, and gastric dysrhythmias after intra-abdominal complications [19]. Regarding surgical procedures, antimesenteric reconstruction [19], vertical reconstruction [20], antecolic reconstruction [21], and stapled Roux-en-Y reconstruction [22] were reported to decrease the incidence of DGE. Our results demonstrated that the incidence of DGE increased significantly in the high-discharge group compared to that in the low-discharge group; however, the reasons cannot be fully explained.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the incidence of DGE was significantly associated with the incidence of pancreatic fistula, which is a well-recognized risk factor of DGE [11,19] . The incidence of DGE was also associated with the small main pancreatic duct diameter, which is a major risk factor for pancreatic fistula [20] .…”
Section: Discussionmentioning
confidence: 87%